The Influence of Bank Health on Third Party Fundraising with Inflation as Intervening Variable at Sharia Commercial Banks in indonesia - Akbar, Ali; Syekh, Saiyid (Dinasti Publisher, 2021)
This research is to know the effect of Bank Health partially and simultaneously on Inflation, the effect of Bank Health partially and simultaneously on Third Party Fundraising, the effect of Inflation on Third Party Fundraising and the effect of Bank Health partially and simultaneously on Third Party Fundraising through Inflation. The population of this research amount of was 14 Sharia Banks in Indonesia for the period 2014 - 2019 with sample amount of 8 Sharia Banks. The method used is Path Analysis by using SPSS program or software with version 22. The results showed that partially the Non Performing Financing (NPF) has negative and insignificant effect on Inflation, Good Corporate Governance (GCG) has positive and insignificant effect on Inflation, Net Rewards has positive and significant effect on Inflation and Capital Adequacy Ratio (CAR) has negative and significant effect on Inflation, while simultaneously Bank Health have no significant effect on Inflation. NPF has positive and significant effect on Third Party Fundraising, GCG has negative and insignificant effect on Third Party Fundraising, Net Rewards has positive and insignificant effect on Third Party Fundraising and CAR has negative and significant effect on Third Party Fundraising, while simultaneously Bank Health have significant effect on Third Party Fundraising. Inflation has negative and insignificant effect on Third Party Fundraising. Partially NPF, GCG, Net Rewards and CAR, indirectly has no significant effect on Third Party Fundraising through Inflation, while simultaneously Bank Health indirectly have no significant effect on Third Party Fundraising through Inflation.